Gauging the Educational Potential of Feminist Inroads into Science - Bansal, Deepika (JOURNAL OF INDIAN EDUCATION, 2019)
Beginning with documenting the near absence of women from conventional histories of science, to casting doubt over popular perception that associates reason, mind and objectivity with the male, and emotion, body and subjectivity with the female, feminists have identified sciences as both a source and a locus of other kinds of gender inequalities. The impact of such critiques, however limited, on certain disciplines cannot be ignored and that paves the way for questioning the nature of science as it presents itself and for putting forth viable alternatives. This paper maps the journey of this kind of a scholarship and discusses what has been its impact on three disciplines of archaeology, evolutionary biology, and primatology, and explores the educational role such feminist ideas play.